2020
DOI: 10.1002/cne.25064
|View full text |Cite
|
Sign up to set email alerts
|

OFF bipolar cell density varies by subtype, eccentricity, and along the dorsal ventral axis in the mouse retina

Abstract: The neural retina is organized along central-peripheral, dorsal-ventral, and laminar planes. Cellular density and distributions vary along the central-peripheral and dorsalventral axis in species including primates, mice, fish, and birds. Differential distribution of cell types within the retina is associated with sensitivity to different types of damage that underpin major retinal diseases, including macular degeneration and glaucoma. Normal variation in retinal distribution remains unreported for multiple ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 63 publications
3
9
0
Order By: Relevance
“…Traditional immunofluorescence (IF) was performed to label RBCs, cone bipolar cells (CBCs), and M€ uller glia in age-matched mice and showed that cells classified by IF or SABER-FISH had nearly identical locations (Figure S2H). The average density of classified bipolar cells was 40,592 ± 5,806 bipolar cells/mm 2 (mean ± SD across retinas), which agrees with the previous estimate of 39,975 ± 6,339 bipolar cells/mm 2 based on a combination of transgenic mouse lines and type-specific antibodies (Figure S2I) (Camerino et al, 2021;Nadal-Nicola ´s et al, 2020;Wassle et al, 2009). These data validate the use of combinatorial SABER-FISH to classify cell populations.…”
Section: Capturing the Complete Diversity Of Bipolar Subtypes In Situsupporting
confidence: 89%
“…Traditional immunofluorescence (IF) was performed to label RBCs, cone bipolar cells (CBCs), and M€ uller glia in age-matched mice and showed that cells classified by IF or SABER-FISH had nearly identical locations (Figure S2H). The average density of classified bipolar cells was 40,592 ± 5,806 bipolar cells/mm 2 (mean ± SD across retinas), which agrees with the previous estimate of 39,975 ± 6,339 bipolar cells/mm 2 based on a combination of transgenic mouse lines and type-specific antibodies (Figure S2I) (Camerino et al, 2021;Nadal-Nicola ´s et al, 2020;Wassle et al, 2009). These data validate the use of combinatorial SABER-FISH to classify cell populations.…”
Section: Capturing the Complete Diversity Of Bipolar Subtypes In Situsupporting
confidence: 89%
“…Slightly higher density of OFF subtypes were observed in the ventral retina compared to the dorsal retina, consistent with previous analyses (Supplementary Fig 1I) [9]. Similarly, slightly higher ventral density of Type 9 was observed, consistent with a recent observation of ventral enrichment for this S-cone selective subtype (Supplementary Fig.…”
Section: Resultssupporting
confidence: 91%
“…Asymmetric distribution of OFF bipolar cells in the retina has been shown by Camerino et al (2021) . They reported that five types of bipolar cells occurred at a higher density in the ventral retina than in the dorsal retina.…”
Section: Resultsmentioning
confidence: 95%
“…Type-dependent, diverse functional architecture is suggested for achromatic cells, such as motion detection ( Euler et al, 2014 ; Hellmer et al, 2021 ). Bipolar cell topography was investigated by Camerino et al (2021) , which revealed that many types of OFF bipolar cells occurred at a higher density in the ventral retina than in the dorsal retina. However, the topography of other types of bipolar cells has not been investigated.…”
Section: Introductionmentioning
confidence: 99%